2021
DOI: 10.30997/ijar.v2i1.100
|View full text |Cite
|
Sign up to set email alerts
|

Survival Analysis of Under-Five Children With Severe Acute Malnutrition in Woldia Hospital: Retrospective Cohort Study

Abstract: Abstract Background: Globally, 52 million children of age under five years were affected by acute malnutrition from which 17 million were severely wasted. In Ethiopia every month over 25,000 children with severe acute malnutrition are admitted to hospitals, if not identified early and treated properly, these children could die. Therefore this study aimed to assess the determinants of time to death of under-five children with SAM admitted to inpatient therapeutic feeding center in Woldia General Hospital.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 6 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…Out of 346 patients, 223 (64.4%) died. 10 Younger age (<24 months) was associated with a 33% shorter expected survival time, and younger children were at a higher risk of mortality due to lower immunity, increased vulnerability to illnesses, and inadequate feeding practices. This was consistent with Jarso et al's research,which indicated that they had a twofold increased risk of passing away earlier.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Out of 346 patients, 223 (64.4%) died. 10 Younger age (<24 months) was associated with a 33% shorter expected survival time, and younger children were at a higher risk of mortality due to lower immunity, increased vulnerability to illnesses, and inadequate feeding practices. This was consistent with Jarso et al's research,which indicated that they had a twofold increased risk of passing away earlier.…”
Section: Discussionmentioning
confidence: 99%
“…The study revealed that out of the 322 SAM children included in the analysis, 118 (36.6%) died, which was higher compared to previous studies conducted in Ethiopia. Out of 346 patients, 223 (64.4%) died 10 . Younger age (<24 months) was associated with a 33% shorter expected survival time, and younger children were at a higher risk of mortality due to lower immunity, increased vulnerability to illnesses, and inadequate feeding practices.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations